2005
DOI: 10.1007/s10681-005-5231-y
|View full text |Cite
|
Sign up to set email alerts
|

Sources of resistance to diseases of sugar beet in related Beta germplasm: II. Soil-borne diseases

Abstract: SummaryBetween 580 and 700 accessions of related cultivated and wild species of the genus Beta were assessed for resistance to four soil-borne diseases of sugar beet: two seedling damping-off diseases caused by the fungi Aphanomyces cochlioides and Pythium ultimum and two diseases of more mature plants, Rhizoctonia root and crown rot, caused by the fungus R. solani, and Rhizomania, caused by Beet necrotic yellow vein virus (BNYVV), a furovirus transmitted by the plasmodiophorid Polymyxa betae. Analysis of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…In Europe, public and private plant breeders, working collaboratively through the IIRB Genetics and Breeding Working Group, are developing ''Doggett'' buffer populations (Doggett and Eberhart 1968) to introgress wild beet sources of disease resistance into the sugar beet gene pool (described in Frese et al 2001;Frese 2002). Additionally, in Europe, evaluation funded through the European Union project-GENRES CT95 42 evaluated between 300 and 700 accessions for resistance to seedling diseases (caused by Aphanomyces cochlioides, Phoma betae), leaf diseases (caused by Cercospora beticola, Erysiphe betae, Beet yellows virus, Beet mild yellowing virus), and root diseases (caused by Beet necrotic yellow vein virus and Rhizoctonia solani) (Luterbacher et al 2004(Luterbacher et al , 2005Panella and Frese 2003;Panella and Lewellen 2005). Private and public plant breeders in Europe and throughout the world are introgressing these novel sources of disease resistance into sugar beet (Asher et al 2001;Biancardi et al 2002;Luterbacher et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, public and private plant breeders, working collaboratively through the IIRB Genetics and Breeding Working Group, are developing ''Doggett'' buffer populations (Doggett and Eberhart 1968) to introgress wild beet sources of disease resistance into the sugar beet gene pool (described in Frese et al 2001;Frese 2002). Additionally, in Europe, evaluation funded through the European Union project-GENRES CT95 42 evaluated between 300 and 700 accessions for resistance to seedling diseases (caused by Aphanomyces cochlioides, Phoma betae), leaf diseases (caused by Cercospora beticola, Erysiphe betae, Beet yellows virus, Beet mild yellowing virus), and root diseases (caused by Beet necrotic yellow vein virus and Rhizoctonia solani) (Luterbacher et al 2004(Luterbacher et al , 2005Panella and Frese 2003;Panella and Lewellen 2005). Private and public plant breeders in Europe and throughout the world are introgressing these novel sources of disease resistance into sugar beet (Asher et al 2001;Biancardi et al 2002;Luterbacher et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sources are commonly wild plant populations and will require transfer to commercially relevant plant genotypes. Novel sources of resistance to Rhizoctonia solani were identified in a screening of wild Beta germplasm (Luterbacher et al 2005) and polygenic resistance to Rhizoctonia root rot was identified in sugar beet (Beta vulgaris L.; Panella 1998). Evaluation of 16 apple (Malus domestica Borkh.)…”
Section: Changes In Conventional Approaches-indirect Selectionmentioning
confidence: 99%
“…fumigant methyl bromide) and the continuous development of pesticide tolerance in several pests have prompted plant breeders to develop pest-resistant cultivars as an important part of integrated pest management systems. Since the 1980s, programmes for largescale Beta germplasm collections and multiple parameter evaluations including pest tolerance, disease resistance and productivity have been carried out in several laboratories to enable sustainable sugar beet breeding and to broaden its genetic base (Doney & Whitney, 1990;Zhang & Liu, 1998;Asher et al, 2001;Frese et al, 2001;Luterbacher et al, 2005;. Sources of resistance to pests, for example nematodes, are frequently found in wild Beta species and have been introgressed into sugar beet through interspecific hybridisation (reviewed by Savitsky, 1975;Brandes et al, 1987;Van Geyt et al, 1990;Yu, 2005;.…”
Section: Introductionmentioning
confidence: 99%